Intermediate disturbance promotes invasive ant abundance. (June 2015) - Vonshak, Merav; Gordon, Deborah M.
Graphical abstract: Highlights: We studied ant communities along an urban–rural gradient. Species richness was highest at the natural and urban habitats. Invasive ant abundance was highest in semi-natural habitats. In semi-natural habitats invasive ants out-compete native ant species. Other alien ants control invasive ant populations in urban habitats. Abstract: Urban habitats are undergoing a faunal and floral homogenization process worldwide. We investigated how such homogenization influences ant communities. We monitored ant species richness and abundance in natural, semi-natural, urban, and agricultural habitats for one year, along an urban–rural gradient in the San Francisco Bay Area, and examined which human-related and other environmental variables most affect ant distribution. We investigated whether alien ant species have an advantage in human-modified habitats. We found that distance from buildings was the most important factor affecting ant distribution. In total, we recorded 17 ant species, of which four were non-native. Native ant species richness was highest in natural habitats, and alien species richness was highest in urban habitats. Remarkably, in a sample of 19, 450 ant workers at food baits, the highest ant abundance across all seasons was in the semi-natural habitat where usually only the invasive Argentine ant ( Linepithema humile ), representing 81% of all ants seen at baits, and the native winter ant ( Prenolepis imparis ) were present. Agricultural habitats had a surprisingly high number of native and alien species. It appears that the invasive Argentine ant creates a favorable ecological community in semi-natural environments, where they compete successfully with the native species, and do not face the increased competition with other alien species that they encounter in urban habitats. Even well protected natural habitat may be favorable for invasive species, due to its proximity to human disturbance.